Effects of infill walls and floor diaphragms on the dynamic characteristics of a narrow-rectangle building. - Pan, Tso-Chien (Earthquake engineering & structural dynamics.)
Most buildings in Singapore are lightly reinforced concrete structures, which are mainly designed for gravity loading only, because Singapore is an island country located in a low-to-moderate seismic region. The dynamic properties of a typical high-rise residential building with a long, narrow rectangular floor plan are studied using both experimental and numerical methods. The effects of the brick infill walls and the flexible diaphragms on the dynamic characteristics of the building are discussed in detail. The results from the ambient vibration tests are correlated with the numerical results of three different finite element models with different levels of sophistication. They include a bare frame model, a frame model with brick infill walls, and a frame model with both brick infill walls and flexible diaphragms. The dynamic properties of the third model match very well with the measured results in terms of both the natural frequencies and the mode shapes. The correlation results demonstrate the respective effects of the brick infill walls and the flexible diaphragms on the dynamic characteristics of the narrow-rectangle building structure.